Complexity, Efficiency, and Fairness of Multi-Product Monopoly Pricing - Eugenio J. Miravete; Katja Seim; Jeff Thurk (Center for Economic Studies and ifo Institute (CESifo), 2014)
The Pennsylvania Liquor Control Board administers the purchase and sale of wine and spirits and is mandated to charge a uniform 30% markup on all products. We use an estimated discrete choice model of demand for spirits, together with information on wholesale prices, to assess the implications of this policy. We find that failure to account for the correlation between demographics and consumption patterns leads to lower prices than those charged by a profit-maximizing, multi-product monopolist. Using product-specific markups leads to higher prices on average, less quantity consumed, an 11% increase in total profits, and greater welfare. The current one-size-fits-all pricing rule ignores variations in demand elasticities resulting in the implicit taxation of high-income and educated households by raising the prices of spirits they prefer (vodka and whiskey) while lowering the price of products favored by low-income and minority households (gin and rum).
Keywords: L12; L21; L32; 330; multi-product price discrimination; complex pricing; taxation by regulation